2021
DOI: 10.1093/jtm/taab066
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 genomic surveillance in Northeast Brazil: timing of emergence of the Brazilian variant of concern P1

Abstract: Since March 2020, 11 lineages of severe acute respiratory syndrome coronavirus 2 have been identified in Sergipe state, Northeast Brazil. During the first 6 months of coronavirus disease 2019 (COVID-19) outbreak, there was a higher frequency of B.1 (58.5%) and B.1.1.33 (17.1%) lineages. During the second wave of COVID-19, there was an increased frequency of P.1 (55.6%), the new Brazilian variant of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
3
14
0
1
Order By: Relevance
“…Similarly, other studies have reported cases of reinfection in essential service workers such as health professionals [19,20]. It is also worth highlighting the occurrence of the Brazilian variant P1 in the period of development of this study, further reinforcing the possibility of reinvention by SARS-CoV-2 [21].…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, other studies have reported cases of reinfection in essential service workers such as health professionals [19,20]. It is also worth highlighting the occurrence of the Brazilian variant P1 in the period of development of this study, further reinforcing the possibility of reinvention by SARS-CoV-2 [21].…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, genomes originating in Brazil formed an isolated clade, probably for two reasons, such as the isolation that the other countries of the globe imposed on their air traffic with Brazil as well as the emergence of local variants such as P1 that quickly became the majority in the territory among Brazilian population, as can be seen from recently published epidemiological studies on this viral strain (Dos Santos et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Gamma or P1 variant, also known as the Brazilian variant, was first reported in November 2020 in Brazil [52]. According to research, the Gamma variant is derived from B.1.1.28 [53]. Studies on the Gamma variant have shown that this species is 1.7-2.4 times more frequent than other species in Brazil.…”
Section: Sars-cov-2 Gamma Variant (Lineage P1)mentioning
confidence: 99%